Ensemble Digital Terrain Model (EDTM) of the world - Yu Feng HO; Tomislav Hengl; Leandro Parente (Zenodo, 2023)
Layers include: Ensemble Digital Terrain Model (EDTM) in 250-m resolution. Unit is in metre(m) and precision is in decimetre (dm).Maps are downscaled from 30-m resolution to 250-m in order to fit the size limit. We provide 30-m EDTM and its standard deviation as links: 30-m EDTM https://s3.eu-central-1.wasabisys.com/openlandmap/dtm/dtm.bareearth_ensemble_p10_30m_s_2018_go_epsg4326_v20230221.tif Standard deviation https://s3.eu-central-1.wasabisys.com/openlandmap/dtm/dtm.bareearth_ensemble_std_30m_s_2018_go_epsg4326_v20230221.tif Derived using ALOS AW3D , GLO-30 , MERITDEM , and national DTMs. We derived a lower 10% quantile from all maps. In order to create bare earth data, we used canopy height (canopy height > 2m)and standard deviation (sd > 6m) to mask building and forest inAW3D andGLO-30. Practical processing is written here in Python. To access and visualize maps use: OpenLandMap.org If you discover a bug, artifact or inconsistency, or if you have a question please use some of the following channels: Technical issues and questions about the code: https://gitlab.com/openlandmap/global-layers/-/issues General questions and comments: https://disqus.com/home/forums/landgis/ All files internally compressed using "COMPRESS=DEFLATE" creationoption in GDAL in Cloud Optimised GeoTiff (COG). File naming convention: dtm.bareearth = variable: digital terrain model (m),bare earth ensemble= determination method: ensemble of mutli-source dsm and dtm p10/std = aggregation/statistics method: 10th percentile / standard deviation 250m = spatial resolution / block support: 250m, s = vertical reference: at surface, go = bounding box:global land without Antarctica epsg.4326 = ESPG code:epsg.4326 v20230221= version code: creation date20230221